National and International Guidelines for Patient Blood Management in Obstetrics: A Qualitative Review. Issue 3 (June 2017) - Shaylor, R.; Weiniger, C. F.; Austin, N.; Tzabazis, A.; Shander, A.; Goodnough, L. T.; Butwick, A. J.
Abstract : (Abstracted from Anesth Analg, 124:216–232, 2017) With increasing rates of transfusions required during childbirth in resource-rich countries such as the United States, patient blood management (PBM) gains importance in addressing postpartum hemorrhage (PPH) in the obstetric setting. Several national obstetric societies have come up with PBM guidelines, but they have not been uniform in their approach.